Defect Detection in Pipelines during Operation Using Magnetic Flux Leakage and Phased Array Ultrasonic Method - Konar, Radoslav; Mician, Milos; Hlavaty, Ivo (Manufacturing Technology Journal, 2014)
The present article is focused on the non-destructive testing (NDT) inspection of pipelines during operation namely Magnetic Flux Leakage (MFL) method and Phased Array ultrasonic (PA) method. MFL inspection technique is electromagnetic test method primarily used to detect flaws or defects in high-permeability of ferromagnetic metals such as carbon steel tubing, plate, wire rope and tubular parts. PA ultrasonic method is an advanced NDT method that is used to detect component failures i.e. cracks or flaws and thereby determine component quality. Due to the possibility to control parameters such as beam angle and focal distance, this method is very efficient regarding to the defect detection and speed of testing. In this article real pipeline defect was identified by MFL method in the internal pipe inspection. This defect was fully mapped by Phased Array ultrasonic method in the terrain. 3D model of defect in the tested material was created from measured data and obtained by PA method. The real dimensions of the defect determined from measurements by the method of MFL and PA are compared.
Keywords: Non-destructive Testing; Magnetic Flux Leakage; Phased Array; Gas Pipeline Inspection